xy=-2
x+y=6
minnus x from second equation
y=6-x
sub for y
x(6-x)=-2
6x-x^2=-2
add x^2 both sides and minus 6x both sides
0=x^2-6x-2
use quadatic formula
if you have
ax^2+bx+c=0
x=[tex] \frac{-b+/- \sqrt{b^{2}-4ac} }{2a} [/tex]
x^2-6x-2=0
a=1
b=-6
c=-2
x=[tex] \frac{-(-6)+/- \sqrt{(-6)^{2}-4(1)(-2)} }{2(1)} [/tex]
x=[tex] \frac{6+/- \sqrt{36+8} }{2} [/tex]
x=[tex] \frac{6+/- \sqrt{44} }{2} [/tex]
x=[tex] \frac{6+/- 2\sqrt{11} }{2} [/tex]
x=[tex] 3+/- \sqrt{11} [/tex]
x=[tex] 3+ \sqrt{11} [/tex] or x=[tex] 3- \sqrt{11} [/tex]
aprox
x=6.31662 or -0.316625
those are the numbers
6.31662 and -0.316625